Constructions of older people and their care during the coronavirus pandemic in Ireland: A Grounded Theory analysis of official discourses - Schulmann, Katharine Ann (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2023)
Beginning in March 2020, the Irish government implemented among Europe's most stringent and sustained lockdown measures to mitigate the spread of Covid-19. Identified early on as a group at particularly high risk, older persons living in the community were instructed to self-isolate at home and older people living in nursing homes were locked down and locked in for extended periods of time. Despite the strict isolation measures, at the one-year mark, 63 percent of fatalities linked to outbreaks in Ireland had occurred among nursing home residents, raising critical questions about the government?s response. This qualitative study set out to analyse social constructions of older people and their care in the official discourses emerging around the government's pandemic response. The rationale being that a discursive analysis of such social constructions might tell us something original and insightful about the structures and processes through which power is exercised in such crisis situations, the power relations involved in decision-making related to older persons and their care, the actors driving the discourses, and crucially, the actors whose voices are not heard. Working within a Critical Realist ontological framework, the study applies a novel blend of Grounded Theory (GT) methodology. It draws on Clarke's (2005) Situational Analysis variant of GT to come to grips with the discursive situation under study, and on Charmaz's Social Constructionist GT (Charmaz, 2006) to identify the structures and processes at work in the construction of older persons in the discourses. Official government texts, collected from the websites of multiple agencies and branches of government, as well as select texts from non-governmental, civil society organisations and private/voluntary associations comprise the discursive data analysed. The data collection period spans January 2020 to March 2021, from first mention of the coronavirus in official Irish documents, to the point at which the rollout of the vaccine among older age groups was documented and discussed. Two main conceptual categories emerged over the course of the data analysis. The first speaks to silences and absences in the discourses, to the near total marginalisation of older persons' voices by dominant medical professionals-as-experts, appointed by and reporting to the state's executive branch. This marginalisation is effected through the prominent construction of older people's vulnerability and dependence, and their constructed lack of autonomy and agency. The second conceptual category, continuities and discontinuities, sees the virus emerge from the discourses as a powerful disruptor and catalyst for innovation, providing the government with the opportunity and momentum to reform the country's beleaguered health and social care systems once and for all. Yet ultimately, the analysis suggests that the virus-pandemic underscores a regression, a reversion to type, if not a continuity, in the state's attitudes towards and treatment of older members of the population. In fact, the construction of older persons as a vulnerable group obscures the very real institutional vulnerability of Ireland's health and social care infrastructure, a vulnerability born of several decades of under-investment and under-development by the public sector. Several factors have influenced this trajectory, not least entrenched social and political norms that define care for older adults as the responsibility of family members and the local community in the first order, attesting to the indelible imprint of Catholic social teaching, notably the principle of subsidiarity, on Ireland's social welfare system.
APPROVED
Keywords: Aging; Covid-19; Coronavirus; Discourse analysis; Social care; Grounded Theory; Care; Social Policy; Vulnerability